What, and Where, is Feminist Security Studies? - Sjoberg, Laura (Journal of Regional Security, 2018)
This piece looks to backwards and forwards to what feminist work in security was, is, and could be, pairing a historical sociology with a forward-looking view of the future(s) of the field. It begins with thinking about feminist studies of security before FSS as a foundation for the discussion, then traces different claims to core identities of FSS. It then looks at divergent strands of FSS, as well as omissions and critiques. Rather than looking to reconcile those differ- ent accounts, it asks what can be taken from them to engage potential futures for FSS, and its contribution to feminisms and/or studies of security.